Hubungan Pengetahuan Dan Dukungan Keluarga Dalam Pencegahan Osteoporosis Pada Pra Lansia Di Wilayah Kerja Puskesmas Tanjung Agung Kabupaten Rejang Lebong Tahun 2023 - Novalion Novalion; Murwati Murwati; Handi Rustandi (Universitas Dehasen Bengkulu, 2023)
Aging is a process of decreasing the ability of tissues to repair themselves or replace themselves, maintain normal structure and function slowly, so that they can withstand injury (including infection) and can repair the damage suffered. When aging occurs the bone density process decreases, the decrease in bone density is called osteoporosis (Darmojo, 2015). Knowing the Relationship between Knowledge and Family Support in Preventing Osteoporosis in Pre-Elderly in the Working Area of the Tanjung Agung Health Center, Rejang Lebong Regency in 2023. This type of research is analytical research using this type of research is analytical research using a cross-sectional design (Hidayat, 2012). The population of this study were families who had pre elderly aged 45-59 at the Tanjung Agung Health Center in 2022 totaling 100 people. the number of samples in this study were 50 respondents. The results of this study indicate that almost half of the respondents 23 (46%) had insufficient knowledge about the prevention of osteoporosis, most of the respondents 39 (78%) had supportive family support, Most of the respondents 39 (78%) had supportive family support, more than half of the respondents 29 (58%) had moderate osteoporosis prevention, there was a significant relationship between family knowledge and prevention of osteoporosis in the pre-elderly, there was a significant relationship between family support and prevention of osteoporosis in the pre-elderly at Pukesmas Tanjung Agung Rejang Lebong Regency in 2023. The results of this study are recommended to the health center to provide more frequent counseling to families regarding the prevention of osteoporosis in the pre-elderly.